Migration and Religion IMISCOE Short Reader - Nordin, Magdalena (IMISCOE Research Series, 2023)
This open access book introduces research on migration and religion with the focus on migration to western European countries from the 1950s and onwards. The book is an in-depth presentation of the main research trends as to methods, theories and empirical zones on migration and religion. In a unique way, the book brings together research about the topic aligning it with the experiences and urgencies of migrants. The first part of three introduces key concepts and presents main research trends over time. The second part deals with the processes of establishment - on an individual level as well as on a group and society level. The third and final part focuses on religious change in relation to religious ideas and habits. It further highlights religious creativity. The third part finishes with a discussion about challenges to research and what we still do not know enough about.